2017
DOI: 10.1021/jacs.6b12950
|View full text |Cite
|
Sign up to set email alerts
|

Unbinding Kinetics of a p38 MAP Kinase Type II Inhibitor from Metadynamics Simulations

Abstract: Understanding the structural and energetic requisites of ligand binding toward its molecular target is of paramount relevance in drug design. In recent years, atomistic free energy calculations have proven to be a valid tool to complement experiments in characterizing the thermodynamic and kinetic properties of protein/ligand interaction. Here, we investigate, through a recently developed metadynamics-based protocol, the unbinding mechanism of an inhibitor of the pharmacologically relevant target p38 MAP kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
231
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 204 publications
(240 citation statements)
references
References 70 publications
(173 reference statements)
6
231
1
2
Order By: Relevance
“…Our study suggests that using only the distance between the ligand and the binding cavity on p38α fails to describe the unbinding process properly, which has also been reported by others recently. 33 Remarkably, for well-converged metadynamics FE simulations ( Figure S1), the choice of two different sets of CVs lead to similar results in terms of thermodynamics and kinetics, which could be considered as a validation of our approach.…”
Section: Selections Of Simulation Models and Slow Motionsmentioning
confidence: 66%
See 1 more Smart Citation
“…Our study suggests that using only the distance between the ligand and the binding cavity on p38α fails to describe the unbinding process properly, which has also been reported by others recently. 33 Remarkably, for well-converged metadynamics FE simulations ( Figure S1), the choice of two different sets of CVs lead to similar results in terms of thermodynamics and kinetics, which could be considered as a validation of our approach.…”
Section: Selections Of Simulation Models and Slow Motionsmentioning
confidence: 66%
“…applied metadynamics and Markov state model to compute the kinetic rates of one inhibitor unbinding from p38α with residence time of a few seconds. 33 A systematic study of a series of inhibitors spanning a wide range of unbinding kinetics and exhibiting diverse structural features could provide further guidance to therapeutic design. However, it is quite challenging and even prohibited to compute the kinetic rates accurately for complex systems and slower unbinding processes with currently available methodologies and compute resources.…”
Section: Introductionmentioning
confidence: 99%
“…Metadynamics-based protocol was developed to investigate the unbinding mechanism of an inhibitor of the pharmacologically relevant target p38 MAP kinase. The result of calculations showed that the salvation of the ligand and of the active site played crucial roles in the unbinding process and demonstrating that metadynamics could be a powerful tool in designing new drugs with engineered binding/unbinding kinetics [25].…”
Section: Introductionmentioning
confidence: 99%
“…11-13 These give direct observations of kinetic information [14][15][16][17][18][19][20] -not just the unbinding rate constant, which experiments can measure reliably, but also other entities which are very hard to obtain from experiments, such as unbinding pathways, intermediate states, their residence times, and the ratedetermining steps.…”
mentioning
confidence: 99%
“…22 We expect and find that considering the dimer instead of tetramer brings down the residence time from more than a day to around a second, which is a timescale regime where the enhanced sampling methods of this work have been shown to be reliable. [14][15][16] Note that there is no fundamental reason why these methods should not work for much longer timescales, and this will be the subject of future investigations. For the tetrameric biotin-streptavidin system the WT and N23A have been reported to have k of f of 4.4 ± 0.3 × 10…”
mentioning
confidence: 99%